Visible-Light-Induced Decarboxylative C–H Adamantylation of Azoles at Ambient Temperature - Koeller, Julian; Gandeepan, Parthasarathy; Ackermann, Lutz (Synthesis, 2019)
The visible-light-promoted oxidant-free decarboxylative C–H adamantylation of azoles was accomplished under ambient reaction conditions. The novel acridinium photocatalyst and cobalt synergistic catalysis enabled the C–H adamantylation under oxidant-free reaction conditions. This C–H adamantylation strategy proved viable for a wide range of substituted azoles, including benzothiazole, benzoxazole, and benzimidazoles as well as caffeine derivatives, providing an expedient access to 2-adamantyl-substituted azoles.
Keywords: photocatalysis; C–H functionalization; decarboxylation; cobalt; acridinium salts; oxidant-free; adamantylation; azoles